The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1007/bf00187257
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of sucrose preference by chronic unpredictable mild stress, and its restoration by a tricyclic antidepressant

Abstract: Rats exposed chronically (5-9 weeks) to a variety of mild unpredictable stressors showed a reduced consumption of and preference for saccharin or sucrose solutions. Preference deficits took at least 2 weeks to develop and were maintained for more than 2 weeks after termination of the stress regime. Sucrose preference was unaffected by 1 week of treatment with the tricyclic antidepressant DMI but returned to normal after 2-4 weeks of DMI treatment. DMI did not alter sucrose preference in unstressed animals. No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

55
1,188
10
43

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,718 publications
(1,296 citation statements)
references
References 29 publications
55
1,188
10
43
Order By: Relevance
“…There were significant decreases in sucrose preference in depressive animal induced by CUMS as expected (po0.001; Willner et al, 1987;De Vry and Schreiber, 1997;Willner, 1997). Treatment with 54 mg/kg/ day mifepristone in the last 7 of 21 days of CUMS significantly increased sucrose preference (po0.01), whereas 4.5 mg/kg/day mifepristone had no obvious effect on sucrose preference (Figure 1).…”
Section: Sucrose Preference Testsupporting
confidence: 75%
See 2 more Smart Citations
“…There were significant decreases in sucrose preference in depressive animal induced by CUMS as expected (po0.001; Willner et al, 1987;De Vry and Schreiber, 1997;Willner, 1997). Treatment with 54 mg/kg/ day mifepristone in the last 7 of 21 days of CUMS significantly increased sucrose preference (po0.01), whereas 4.5 mg/kg/day mifepristone had no obvious effect on sucrose preference (Figure 1).…”
Section: Sucrose Preference Testsupporting
confidence: 75%
“…In the present study, we used the rat model of depression induced by CUMS, which mimic a series of life events. CUMS has shown to produce behavioral and neuroendocrine changes in rats similar to major depression in human (Willner et al, 1987;De Vry and Schreiber, 1997;Willner, 1997). Patients with psychotic major depression are characterized by abnormalities in the HPA axis activity, for example, elevated urinary free cortisol levels and plasma adrenocorticotropin hormone, as well as the highest rates of nonsuppression on the dexamethasone suppression test (Belanoff et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we observed that rats submitted to chronic administration of H-BCAA have a decreased sweet food intake and increased adrenal gland weight, without any alteration of body weight compared with the control group. This mimics anhedonia, a key depressive symptom (Katz et al 1981b;Willner et al 1987Willner et al , 1998. We also observed an increase in immobility time in the H-BCAA group during the forced swimming test.…”
Section: Discussionsupporting
confidence: 63%
“…The CUS procedure is a modification of published procedures (Katz et al, 1981;Lu et al, 2006;Willner et al, 1987). One day before beginning the chronic unpredictable stress, rats were housed individually, and the CUS procedure was then applied for 14 consecutive days, as outlined in Table 1.…”
Section: Chronic Unpredictable Stress Proceduresmentioning
confidence: 99%